The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/met.1969
|View full text |Cite
|
Sign up to set email alerts
|

How many offshore wind turbines does New England need?

Abstract: The proliferation of countries and regions with 100% clean or renewable energy targets necessitates an analysis to determine the number of generating units and storage needed to meet real‐time electricity demand on the electric grid. The coastal areas of New England have the capacity to produce a large percentage of the region's energy needs with offshore wind turbines. Here we model offshore wind turbine power production data using MERRA‐2 reanalysis and lidar wind speed data sets. We compare this power produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Previous work (Livingston and Lundquist, 2020) assuming a constant 20% wake loss, shown here to be underestimated, suggested that 2,000 10-MW turbines could meet New England's demand 37% of the time. In all, the LA, with 1,418 12-MW turbines, supply 68 TWh year −1 and 71 TWh year −1 , or 1.72% (TKE_0) to 1.65% (TKE_100) of the nation's energy supply.…”
Section: Annual Energy Productionmentioning
confidence: 60%
“…Previous work (Livingston and Lundquist, 2020) assuming a constant 20% wake loss, shown here to be underestimated, suggested that 2,000 10-MW turbines could meet New England's demand 37% of the time. In all, the LA, with 1,418 12-MW turbines, supply 68 TWh year −1 and 71 TWh year −1 , or 1.72% (TKE_0) to 1.65% (TKE_100) of the nation's energy supply.…”
Section: Annual Energy Productionmentioning
confidence: 60%
“…In addition, the level of storage defined in the scenarios might be subject to over planting with respect to the renewable energy resource capacity. As shown by Livingston and Lundquist (2020) the ability to balance the potential of renewable generation with storage has a limit in the order of hours to a few days and additional storage will likely rarely be utilised by renewables.…”
Section: Limitations and Discussionmentioning
confidence: 99%
“…In 2018, the New England region experienced its initial annual escalation in the average wholesale electricity load since 2013 which showed growth of 1.7% compared to the average of 2017. Nevertheless, when adjusting for the weather England region [80] which shows the summertime demonstrated a slightly elevated level of overall energy consumption compared to other seasons throughout the year. Air conditioning is a significant contributor to energy consumption during the warmer months as it is used maintain comfortable indoor temperatures.…”
Section: Time Series Analysismentioning
confidence: 99%